Temporary Pacing Simulator: A Training Tool for Clinicians - Ioana Cretu; Alexander Tindale; Maysam Abbod; Wamadeva Balachandran; Ashraf W. Khir; Hongying Meng (Applied Sciences)
Cardiovascular diseases (CVDs) are the leading global cause of death, impacting nations worldwide. Despite medical advancements, managing patients who require temporary pacing (TP) after cardiac surgery remains challenging. TP devices are essential for stabilizing patients with unstable arrhythmias or post-surgical complications but demand manual adjustments and precise clinician management, unlike permanent pacemakers. There is an urgent need for improved TP training and standardisation, hindered by a lack of formal guidelines and adequate protocols. Existing simulators often omit crucial haemodynamic parameters and complex clinical scenarios, limiting their effectiveness. This paper introduces an advanced Temporary Cardiac Pacing Simulator (TCPS) that provides comprehensive physiological signals and complex scenarios for realistic training. It simulates various pacing modes—atrial, ventricular, and dual-chamber—while modeling pacing failures and haemodynamic changes. Sophisticated algorithms replicate clinical responses, offering real-time feedback and dynamic visualizations to enhance learning. Additionally, an innovative feature optimises atrioventricular (AV) delay settings, crucial for improving patient outcomes in both acute and postoperative care.